Efektivitas Pelayanan Publik Di Dinas Kependudukan dan Catatan Sipil Kabupaten Berau - Rifgi Setia; Rita Kala Linggi; Letizia Dyastari (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
The research aimed to determine the effectiveness of public services at the Population and Civil Registration Office in Berau Regency, with a focus on goal achievement, integration, and adaptation. The research method used was descriptive and qualitative, and data was collected through observation, interviews, and documentation. The study found that the three stages of public service implementation were effective. The achievement of goals for the issuance of birth certificates, e-KTP, and child identity cards (KIA) was high and evenly distributed among the community. The community found it easy to manage their population administration documents and did not have to wait long according to the standard operating procedure (SOP), which is one day. Integration in public service implementation was effective as the Population and Civil Registration Office in Berau Regency worked well with other cross-sector organizations such as the Department of Education, BPS, Banking, and Hospitals. The issuance of birth certificates, e-KTP, and child identity cards was evenly distributed among the community. Adaptation in public service implementation was effective because it met the needs of the community, was easy, and fast. The search results provide additional information related to the Population and Civil Registration Office in Berau Regency, including a strategic plan for the office1 the main goal of fulfilling population administration documents for the community and studies on the implementation of e-KTP policies in Berau Regency